Identification of Key Genes Mutations Associated With the Radiosensitivity by Whole Exome Sequencing in Pancreatic Cancer - Hu, Bin; Ma, Xiumei; Huang, Renhua; Wu, Zheng; Lu, Jun; Guo, Yuntao; Tang, Jianmin; Ma, Chunhui; Ma, Jun; Zhang, Lei; Bai, Yongrui (Frontiers in Oncology, 2021)
Background: Pancreatic cancer (PC) is one of the most lethal human cancers and radiation therapy (RT) is an important treating option. Many patients diagnosed with PC do not achieve objective responses due to the existence of intrinsic and acquired radioresistance. Therefore, biomarkers, which predict radiotherapy benefit in PC, are eagerly needed to be identified. Methods: Whole exome sequencing of six pancreatic ductal adenocarcinoma patients (PDAC) (three with a good response and three with a poor response) who had received radical surgery and then radiotherapy has been performed as standard of care treatment. Somatic and germline variants and the mutational signatures were analyzed with bioinformatics tools and public databases. Functional enrichment and pathway-based protein-protein interaction analyses were utilized to address the possibly mechanism in radioresistance. MTT, LDH and colony formation assay were applied to evaluate cell growth and colony formation ability. Results: In the present study, somatic mutations locate in 441 genes were detected to be radiosensitivity related loci. 17 genes including the Smad protein family members (SMAD3 and SMAD4) were identified to influence the radiosensitivity in PDAC. The SMAD3 and SMAD4 genes mutate differently between radiosensitive and radioresistant PDAC patients. Mutation of SMAD3 potentiates the effects of ionizing radiation (IR) on cell growth and colony formation in PDAC cells, while mutation of SMAD4 had the opposite effects. SMAD3 and SMAD4 regulate the radiosensitivity of PDAC, at least in part, by P21 and FOXO3a, respectively. Conclusions: These results indicate that mutations of SMAD3 and SMAD4 likely cause the difference of response to radiotherapy in PDAC, which might be considered as the biomarkers and potential targets for the radiotherapy of pancreatic cancer.